How to promote changes in primary care? The Florentine experience of the House of Community - Milani, Chiara; Naldini, Giulia; Baggiani, Lorenzo; Nerattini, Marco; Bonaccorsi, Guglielmo (Frontiers in Public Health, 2023)
Primary care (PC) has a central role in promoting health and preventing diseases, even during health emergencies. The COVID-19 pandemic has shown how strengthening comprehensive primary healthcare (c-PHC) services is key to ensuring community health. The Italian government decided to support PHC by investing resources from the Next Generation EU (NextGenEu) plan in the development of local health districts (LHDs) and local PC centers called “Houses of Community (HoC)”. The Florence LHD (Tuscany)—in direct collaboration with the University of Florence—has represented the experimental context in which a c-PHC-inspired organizational model has been proposed and included the HoC as the nearest access point to PC services. Through multiprofessional collaboration practices, HoCs provide continuity of care as well as health and social integration. Different levels of action must coexist to initiate, implement, and sustain this new PC model: the organizational and managerial level, the experimentation of a new model of care, and the research level, which includes universities and LHD through participatory research and action approaches. This process benefits from health professionals' (HPs) participation and continuous assessment, the care for working relationships between HPs and services, an appropriate research methodology together with a “permeable” multidisciplinary research group, and educational programs. In this context, the HoC assumes the role of a permanent laboratory of experimentation in PC, supporting the effectiveness of care and answering what the Next Gen EU plan has been foreseeing for the rethinking of Italian territorial services.